Peningkatan literasi melalui program pojok baca siswa di MI Assalam Batu - Wati, Amelia Rochima (Maliki Interdisciplinary Journal, 2024)
This research is motivated by the number of students who are still lacking in carrying out the literacy movement, where this literacy movement needs to be applied to students who are still studying in MI where they must be accustomed to reading, many of the students are still lacking in literacy. This research uses descriptive qualitative, that UNESCO says Indonesia is second from the bottom regarding literacy, where the interest in reading from Indonesian people is still lacking, so this is our challenge to make students more interested in literacy that can make habits and culture at school. The thing that causes low literacy is the lack of facilities or book collections in the library which makes students less interested in literacy or less interested in visiting the library at school, and low learning motivation in students, from these problems can create a reading corner program that can improve student literacy.